The effect of galactagogue herbal tea on oxidant and anti-oxidant status of human milk. (July 2013) - Kavurt, Sumru; Bas, Ahmet Yagmur; Aydemir, Ozge; Yucel, Husniye; Isıkoglu, Semra; Demirel, Nihal
Abstract Objective: Human milk (HM) has antioxidant constituents which protect newborns against oxidative damage. We aimed to evaluate whether maternal consumption of herbal tea containing fenugreek had any effects on global oxidant and antioxidant capacity of HM. Methods: Volunteer mothers 18–35 years of age without any antenatal or perinatal risk factors were randomly assigned to receive galactagogue herbal tea (Humana still-tee®, Herford, Deutschland) 3 cups/d or same amount of water as placebo. The total antioxidant capacity (TAC), total oxidant status (TOS) and the oxidative stress index (OSI) of breast milk samples taken in the 1st day and 7–10 d were compared between groups. Results: Herbal tea (n = 40) and placebo (n = 40) groups had similar TAC, TOS and OSI values in the 1st day samples. TAC, TOS and OSI values in the breast milk samples taken on 7–10th day were also similar. OSI increased significantly in 7–10 day samples compared to 1st day in each group, while TAC and TOS levels did not differ. Conclusion: Galactagogue herbal tea containing fenugreek has no detectable effect on global oxidant and antioxidant status of HM. OSI increases in course of lactation compared to colostrums irrespective of galactagogue use.